Community dynamics of cellulose‐adapted thermophilic bacterial consortia. (13th June 2013) - Eichorst, Stephanie A.; Varanasi, Patanjali; Stavila, Vatalie; Zemla, Marcin; Auer, Manfred; Singh, Seema; Simmons, Blake A.; Singer, Steven W.
Summary Enzymatic hydrolysis of cellulose is a key process in the global carbon cycle and the industrial conversion of biomass to biofuels. In natural environments, cellulose hydrolysis is predominately performed by microbial communities. However, detailed understanding of bacterial cellulose hydrolysis is primarily confined to a few model isolates. Developing models for cellulose hydrolysis by mixed microbial consortia will complement these isolate studies and may reveal new mechanisms for cellulose deconstruction. Microbial communities were adapted to microcrystalline cellulose under aerobic, thermophilic conditions using green waste compost as the inoculum to study cellulose hydrolysis in a microbial consortium. This adaptation selected for three dominant taxa – the Firmicutes, Bacteroidetes and Thermus. A high‐resolution profile of community development during the enrichment demonstrated a community transition from Firmicutes to a novel Bacteroidetes population that clusters in the Chitinophagaceae family. A representative strain of this population, strain NYFB, was successfully isolated, and sequencing of a nearly full‐length 16S rRNA gene demonstrated that it was only 86% identical compared with other validated strains in the phylum Bacteroidetes. Strain NYFB grew well on soluble polysaccharide substrates, but grew poorly on insoluble polysaccharide substrates. Similar communities were observed in companion thermophilic enrichments on insoluble wheat arabinoxylan, a hemicellulosic substrate, suggesting a common model for deconstruction of plant polysaccharides. Combining observations of community dynamics and the physiology of strain NYFB, a cooperative successional model for polysaccharide hydrolysis by the Firmicutes and Bacteroidetes in the thermophilic cellulolytic consortia is proposed.